PELATIHAN PEMBUATAN PESTISIDA NABATI UNTUK PENGENDALIAN HAMA DAN PENYAKIT TANAMAN DI DESA CUBADAK AIR KECAMATAN PARIAMAN UTARA KOTA PARIAMAN - Yulmira Yanti; Wiwik Suryani; Gliceri Yumidiona; Salsabilla Afisti; Muhammad Iqbal; Ichlasul Farhan Nouvensi; Astri Permata Sari; Ge Gatra Gova Capatagi; Putri Mawar Sari (LPPM Universitas Andalas, 2023)
The excessive and improper use of synthetic pesticides triggers ecosystem damage. The negative impacts of pesticide use can result in pest resistance, resurgence, the death of natural enemies, residue left on crop yields, and environmental pollution. Aside from the negative impacts on the environment, the use of synthetic pesticides burdens farmers due to their relatively high cost. Botanical pesticides become an alternative for controlling plant pests (Pests). Thus, a socialization on making botanical pesticides was conducted in Cubadak Air Village, North Pariaman Subdistrict, Pariaman City. The objective of creating botanical pesticides was to reduce the use of synthetic pesticides, decrease control costs, and maintain agricultural ecosystems. The botanical pesticide-making activity was carried out on July 19-20, 2023, in Cubadak Air Village, North Pariaman Subdistrict, Pariaman City. The method used was a direct demonstration of botanical pesticide production to farmer groups and the community in Cubadak Air Village. The results obtained after empowering the community in making botanical pesticides were that farmers could directly produce these pesticides, thereby aiding in the farmers' economy by reducing pesticide purchasing costs, utilizing wild plants like weeds to be used as botanical pesticides. The training on making botanical pesticides proceeded smoothly, and participants showed enthusiasm for the presented material. The use of environmentally friendly botanical pesticides, utilizing available natural resources, helps to maintain ecosystem balance.